'It's OK to feel totally confused': reflection without practice by preservice teachers in an introductory education course. Issue 5 (2nd September 2016) - Nelson, Frederick L.; Miller, Libbi R.; Yun, Cathy
Abstract: In the following article, we describe our research with preservice teachers (PSTs) engaged in an introductory course in curriculum, instruction, and technology. Typically, efforts to engage PSTs in reflection focus on the student-teaching experience. We assert there is potential for PSTs to think deeply about their identities prior to actual classroom experience. Our research concerns the development of reflective pedagogical thinking by PSTs, stimulated by a variety of curricular, instructional, and technological learning experiences. We will highlight the pedagogical innovations we employed to stimulate PSTs to engage in meaningful reflection prior to their student-teaching experiences. We will describe our learning experiences and nontraditional grading scheme in the course, and examine the impact of those practices on PST reflective writing.